Chemical characterization and bioactivity of the essential oil from Santolina insularis, a Sardinian endemism. Issue 1 (22nd December 2021) - Alves-Silva, Jorge Miguel; Piras, Alessandra; Porcedda, Silvia; Falconieri, Danilo; Maxia, Andrea; Gonçalves, Maria José; Cruz, Maria Teresa; Salgueiro, Lígia
Abstract: Santolina insularis is a Sardinian endemism that is widely used in traditional medicine. The essential oil was obtained with a yield of 2.7% and is mainly characterized by β-phellandrene (22.6%), myrcene (11.4%) and artemisia ketone (7.6%). The oil significantly reduced NO production without affecting macrophages viability. In addition, it substantially inhibited the expression of two key pro-inflammatory enzymes, iNOS and COX-2 (71% and 25% at 0.54 mg/mL). Furthermore, the oil had a promising antifungal activity being Cryptococcus neoformans (MIC = 0.13 mg/mL) and the majority of dermatophytes (MIC = 0.13 mg/mL) the most susceptible fungi. Moreover, it significantly decreased the yeast-to-hypha transition (80% inhibition at 0.13 mg/mL) on C. albicans long before showing inhibitory effects. Overall, these results show that S. insularis could be applied in the treatment of fungal infections and associated inflammatory response. Graphical Abstract: